GANGGUAN EMOSI DAN PERILAKU PADA GILLY HOPKINS DALAM NOVEL THE GREAT GILLY HOPKINS KARYA KATHERINE PATERSON - Lepa, Rocky Aldrian; Sigarlaki, Stephani J.; Marentek, Andriyani (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstractThis research entitled â€œGangguan Emosi dan Perilaku pada Gilly Hopkins dalam The Great Gilly Hopkins karya Katherine Patersonâ€ is intended to fulfill a requirement to accomplish the â€Sarjanaâ€ degree at Faculty of Humanities, Sam Ratulangi University, Manado. It aims at determining emotional and behavioral disorders of the main character, Gilly Hopkins. Gilly was lacking of social skills, could not adjust her emotion, and misbehaved in her social environment. Those personality traits made bad impacts on other people in her surroundings who interacted with her. This study used the theory of emotional and behavioral disorder by Daniel Hallahan and James Kauffman (1988), and employed descriptive method in analyzing the data from the novel. The results show that the main character, Gilly Hopkins has emotional and behavioral disorders by showing her characteristics, such as fighting and beating, teasing and disturbing, shouting, disobeying commands, vandalising, being impolite, being arrogant, being hyperactive, being easily angry or feeling offended, and being a liar. The factor which triggered emotional and behavioral disorders in Gilly is family factors. It gave bad impacts on her surroundings, such as making other people felt dejected, uncomfortable, angry, sad, and involving them into a debate and her bad deeds like stealing. —————————————————– Keyword: Emotional and Behavioral Disorder (EBD), Novel The Great Gilly Hopkins.